Perjanjian Nominee dalam Praktik Jual Beli Tanah - Henry Aspan; Erniyanti; Etty Sri Wahyuni (Syntax Literate, 2023)
The main problem that is of concern to the author in this writing is the practice of controlling land rights through nominee agreements or better known as loan agreements. Where in this agreement foreigners who do not have the authority to own land rights in Indonesia borrow the name of an Indonesian citizen, to purchase a land/land, then Indonesian citizens authorize the foreigner to be able to do anything with the land/ the land. Arrangements for engagements are based on an open system, meaning that everyone may enter into any kind of engagement, both those that have been named and those that have not been named in the law. However, an open system is limited by three things, namely, it is not prohibited by law, it is not contrary to public order, and it is not contrary to decency. Thus it can be seen that the nominee agreement can be said to be contrary to the applicable law, because after all Foreign Citizens cannot have ownership rights to land that is in Indonesian territory. Based on the results of this study, it can be seen that the nominee agreement is based on the bad faith agreement of the parties, and this is contrary to the principle of freedom of contract by not meeting the objective requirements for the validity of an agreement as stipulated in Article 1320 of the Civil Code. Therefore, the nominee agreement is legally invalid and does not have binding legal force, meaning that the nominee agreement can also be interpreted as null and void because one of the legal terms of the agreement is not fulfilled, namely a cause (causa) that is lawful. The causa that is meant by that word is the purpose, namely what is desired by both parties by entering into the agreement. The results of the study found that nominee agreements made by foreigners with Indonesian citizens do not have binding legal force and are null and void, because they have violated laws and regulations regarding ownership of land rights in Indonesia